PENDEKATAN BEHAVIORISME, KOGNITIVISME, KONSTRUKTIVISME, DAN HUMANISME DALAM PEMBELAJARAN DI SEKOLAH DASAR - Tati Qoriana (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2026)
This study aims to examine and analyze four major approaches in learning theory, namely behaviorism, cognitivism, constructivism, and humanism, as well as the relevance of their application in the learning process at the Elementary School (SD) level. The method used is library research by analyzing various relevant primary and secondary literature sources. The findings show that each approach has distinct characteristics, basic assumptions, and pedagogical implications that are different yet complementary. Behaviorism emphasizes the importance of reinforcement and conditioning in shaping student behavior. Cognitivism focuses on internal mental processes and knowledge structures. Constructivism views learning as an active process of constructing knowledge. Meanwhile, humanism places student needs, motivation, and self-potential at the center of learning. In the context of elementary schools, an eclectic and adaptive integration of these four approaches can produce more holistic, meaningful, and student-centered learning. Elementary school teachers need to understand the theoretical foundations of each approach in order to select learning strategies most appropriate to the developmental characteristics of students aged 6-12 years.